PELATIHAN PENGGUNAAN LEARNING MANAGEMENT SYSTEM SEBAGAI UPAYA OPTIMALISASI PEMBELAJARAN HYBRID - Darwanto Darwanto; Rohmani; Karsoni Berta Dinata; Windo Dicky Irawan; Purna Bayu Nugroho (Pengabdian Kepada Masyarakat Cendekia, 2022)
The effectiveness of Distance Learning (PJJ) is not felt by all places. Schools with conditions far from urban areas and limited access to online learning make PJJ not run as expected. This community service aims to contribute to minimizing the impact of the COVID-19 pandemic, which requires online learning and post-pandemic learning. Service activities are designed to bridge the learning process both online and face-to-face. Hybrid learning as a learning solution after the COVID-19 pandemic requires supporting technology so that learning objectives can be achieved. Learning Management system as an alternative to supporting technology for Hybrid learning because of the various advantages in its features that every educator needs to master. Therefore, this service is deemed necessary to be carried out so that teachers can have sufficient competence in using LMS as part of Hybrid learning.